Women's Land Rights in The Gambia: Socio-legal review - Monterroso, I.; Enokenwa Baa, Ojongetakah; Paez Valencia, Ana Maria (CIFOR-ICRAF and International Fund for Agricultural Development, 2021)
This socio-legal analysis provides an overview of existing land governance arrangements in The Gambia as they relate to women’s access to land and resources. It discusses two different types of land tenure interventions: title deeds and certification. These inventions vary according to different types of recognized rights-holders and the area in which rights are being formalized. Access to and control over land and other productive resources in The Gambia is shaped by complex tenure systems. Coexisting and interacting customary systems and statutory regulations are influenced by reform processes, with differentiated effects in rural and urban areas. Rights to resources are often negotiated across multiple rights-holders, overlapping tenure regimes and resource systems. Despite important progress through legislative reforms, implementation has been slow and prevailing barriers and gaps continue to influence the recognition of women’s land rights and their ability to benefit from them.